159k views
3 votes
Extra points// mathematics

Extra points// mathematics-example-1
User Janira
by
5.7k points

2 Answers

3 votes

Answer:

B sqrt(30) =c

Explanation:

The Pythagorean theorem is

a^2 + b^2 =c^2

We know a =2sqrt(3) and b = 3 sqrt(2)

Substituting into the equation

(2sqrt(3))^2 + (3sqrt(2))^2 = c^2

(xy)^2 = x^2 y^2 so

2^2 sqrt(3)^2 + 3^2 sqrt(2)^2 = c^2

4*3 + 9*2 = c^2

12 +18 = c^2

30 = c^2

Taking the square root of each side

sqrt(30) = sqrt(c^2)

sqrt(30) =c


2 votes

Answer:

B

Explanation:

Givens

a = 2 sqrt(3)

b = 3 sqrt(2)

c = ?

Formula

a^2 + b^2 = c^2

Solution

  • (2sqrt(3))^2 = 2*2 * sqrt(3)*sqrt(3)
  • (2sqrt(3))^2 = 4 * 3
  • (2sqrt(3))^2 = 12
  • (3sqrt(2))^2 = 3 * 3 * sqrt(2)*sqrt(2)
  • (3sqrt(2))^2 = 9 * 2
  • (3sqrt(2))^2 = 18

(2sqrt(3)^2 + 3sqrt(2)^2 ) = c^2

4*3 + 9*2 = c^2

12 + 18 = c^2

c^2 = 30

sqrt(c)^2 = sqrt(30)

c = sqrt(30)

Answer

B

User Davie Brown
by
5.2k points